Productivity and American Leadership: A Review Article - Williamson, Jeffrey G. (Journal of Economic Literature, 1991)
WHILE THE U. S. PRODUCTIVITY slowdown wasn't first discovered by economists in 1980, it certainly began to get big play in that year. The American Economic Association devoted a session to the current retardation in U.S. productivity and the first in a series of major articles on the slowdown appeared in this journal. The latter was a review by Richard Stone (1980) of Edward Denison's Accounting for Slower Economic Growth: The United States in the 1970s (1979). Denison documented a substantial drop in the growth of labor productivity between 1948-73 and 197376, showing that the lion's share of that slowdown could be attributed to what had come to be known as the residual, or to what others have called total factor productivity growth. Stone's review of Denison was followed by contributions by Richard Nelson (1981), Roger D. Norton (1986), and Angus Maddison (1987). The citations to literature on the slowdown had ballooned from dozens to hundreds by the appearance of Maddison's article, and it had become everyday fare in our morning newspapers. In the midst of this surge of concern with the U.S. productivity slowdown, William Baumol was asked by the president of the Committee for Economic Development to prepare a statement on productivity policy for the United States. With disarming modesty, Baumol reports the CED was looking for someone whose ignorance of the subject ensured that the statement would not merely recapitulate the accepted shibboleths (p. ix). Baumol accepted the challenge in 1983 and with the appearance of Productivity and American Leadership seven years later he and his collaborators (Sue Anne Batey Blackman and Edward N. Wolff) have produced at least four books and nine articles. A productive collaboration indeed. Why another publication on the slowdown? In 1979, Denison regarded the slowdown as a mystery, and Stone concluded his review with a wistful sigh-If Denison is stumped who can expect to do better? (Stone 1980, p. 1539). A decade later, Baumol, Blackman, and Wolff (hereafter BBW) have shown that we can do a lot better. The book has four important virtues. First, it reveals an appreciation for history. If there ever was a topic for which an understanding of the long run mattered, productivity performance is surely it. United States experience with the productivity slowdown since the 1960s cannot be adequately understood without placing that experience in the perspective of a century of productivity growth, nor can it be * William J. Baumol, Sue Anne Batey Blackman, and Edward N. Wolff. Productivity and American Leadership: The Long View. Cambridge and London: The MIT Press, 1989. Pp. x, 395. $29.95. ISBN 0-262-02293-1.